Analysis of steel‐reinforced masonry walls regarding maximum shear loads / Traglastberechnung von vertikal bewehrten Mauerwerksscheiben. Issue 3 (June 2016) - Stempfle, Hartwig; Weber, Marius; Wipfli, Manuel
Abstract: Loadings on masonry for the earthquake case pose particular challenges for the material. In order to improve the load‐bearing and deformation behaviour, masonry building elements can be strengthened with reinforcement. This article presents an analytical model for the calculation of the load‐bearing capacity of vertically reinforced masonry panels. The masonry is modelled as a homogeneous and anisotropic material and failure conditions are based on the plastic theory. Using uniaxially loaded stress fields and considering the structural constraints, a lower load‐bearing threshold can be given. In order to verify the model, three shear tests on reinforced sand‐lime block masonry were recalculated regarding their load‐bearing capacity. The test panels each contained vertical steel reinforcement in the blocks. The blocks were laid in thin bed mortar.